State, Ulama, and Local Culture: A Trilogy Framework Characterizing Indonesia’s Distinctive Fiqh in the Official Isbat Hearing - Ismail Ismail; Ardiyansyah Ardiyansyah; Muhammad Khalil Mubarraq (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, determining the beginning of the Hijri month is viewed purely as a dogmatic religious procedure. However, in reality, the isbat hilal (crescent moon determination) hearing in Indonesia operates as a complex socio-legal phenomenon fraught with negotiation. This study aims to analyze this process as a distinctive manifestation of Indonesian fiqh (Islamic jurisprudence) that integrates the modern state, traditional religious authority, and local cultural wisdom. Employing a socio-legal approach and a qualitative legal study, this research analyzes government regulations, isbat hearing outcomes, and fatwas of the Indonesian Ulema Council (MUI). The findings reveal that the isbat hilal process forms a non-dichotomous hybrid authority model: the state acts as a constitutive facilitator and final arbiter, the ulema contribute epistemic authority through rukyat (moonsighting) and hisab (astronomical calculation), while the local culture of musyawarah untuk mufakat (deliberation for consensus) transforms it into a dynamic space for negotiation. This study contributes to reinforcing the trilogy framework of Indonesian fiqh, which pragmatically reconciles textual Islamic law, science, and the archipelago's socio-cultural context into a functional legal decision.